PERILAKU HIDUP BERSIH DAN SEHAT MASYARAKAT PEMUKIMAN KUMUH (Slum Area) DI KELURAHAN MERANTI PANDAK KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Rudiansyah "; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Health is state of well being of body, mind and social life that allows person to live socially and economically productive. To achieving healthy principle, the Ministry of Health (Depkes) has established 10 indicators of hygiene behavior and healthy. To achieve that, at least 65% of the people in region that is capable of running the PHBs as a pilot area to implement clean and healthy behaviors.Meranti Pandak village is one of the villagers in Pekanbaru city slums are still there and will be prone to floods. There were 10 RW out of 13 RW classified as slum. This is because density of population making those areas classified as slums.Of the data pekanbaru city health department, noted that districts Rumbai Pesisir an area prone diarrheal disease, one of the most common is in village Meranti Pandak. The case is going on because there are many people in the area who haven’t running clean and healthy living behaviors.As for the purpose of this study was to determine whether people in the area are already running 10 PHBs indicators by the government, as well as find out what the factors that influence them in carrying out these PHBsBased on the result of research on behavior of living clean and healthy (PHBs) it can be seen the people in Meranti Pandak village has not reached the target 65% in running the 10 indicators PHBs. This is because the factors affect the community in running 10 indicators PHBs.Keywords: 10 Indicators PHBs, Health, Hygiene, Factors affecting.